Exploring Intergroup Peer Exclusion: Validation of the Latency Social-Psychological Developmental Questionnaire (LSPD) - Hanna Fisher-Grafy; Sonya Meyer (MDPI AG, 2023)
Intergroup peer exclusion has been studied mainly from a pathological aspect. Currently, methods of diagnosis and treatment focus on this pathological point of view. Qualitative research has revealed that social intergroup peer exclusion has a role in the developmental task of the latency stage. The study's main aim was to develop and validate a quick and easy quantitative questionnaire for use in a school setting that reflects the social developmental variables exposed in previous qualitative research. The 32-item Latency Social-Psychological Developmental questionnaire (LSPD) and the Loneliness and Social Dissatisfaction Questionnaire were administered to 20 Grade 4 and Grade 5 classes at four co-ed public elementary schools (N = 373 participants). Factor analysis revealed six developmental factors, and correlations were found between these factors and loneliness. The LSPD is a tool for assessing latency stage development among children who experienced exclusion as well as the developmental status of the entire class. The LSPD can assist in identifying specific development areas to focus on in treatment and intervention.